Beyond Ecotourism: Measuring the Social Return on Investment of Community-Based Whale Shark Conservation in Kwatisore, Indonesia - Purnomo; Ponco Nugroho; Alih Istik Wahyuni; Nabila Ismasari (PT Sahabat Investasi Indotama, 2026)
Abstract Conventional evaluations of marine conservation programmes, particularly those centred on charismatic megafauna such as whale sharks, tend to equate programme value with tourism revenue, obscuring the substantial social value generated through preventive ecological action, capacity building, and institutional support. This study applies evaluative Social Return on Investment (SROI) methodology, following Social Value International’s Social Value Principles, to assess the Kwatisore Whale Shark Conservation Programme in Cenderawasih Bay National Park, Central Papua, Indonesia, operated by PT Pertamina International Shipping since 2021. Using data from 32 stakeholder informants across seven groups (2023–2025), we mapped fourteen material outcomes spanning ecological monitoring, plastic waste management, community diving safety, cold-chain infrastructure, and conservation education. Total programme investment was IDR 1,079,735,000 (Input), yielding a present value of net outcomes of IDR 2,429,384,408 and an SROI ratio of 2.25:1. Contrary to tourism-centric valuation frameworks, 73% of total social value derives from non-tourism pathways, dominated by the institutional value of scientific monitoring data (59.1%) and preventive avoidance of plastic-exposure risk. Eight sensitivity scenarios, including a 50% decline in whale shark tourist visits, confirm the ratio remains above break-even (minimum SROI = 1.62), demonstrating structural resilience to tourism disruption. These findings support reframing community-based marine conservation as strategic social investment rather than tourism-dependent philanthropy, with implications for conservation finance, corporate ESG risk management, and SDG 14 financing strategies in the Global South. Abstrak Evaluasi konvensional terhadap program konservasi laut, khususnya yang berpusat pada megafauna karismatik seperti hiu paus, cenderung menyamakan nilai program dengan pendapatan wisata, sehingga menyembunyikan nilai sosial signifikan yang dihasilkan melalui tindakan pencegahan ekologis, penguatan kapasitas, dan dukungan kelembagaan. Studi ini menerapkan metodologi evaluatif Social Return on Investment (SROI), mengikuti Prinsip Nilai Sosial dari Social Value International, untuk menilai Program Konservasi Hiu Paus Kwatisore di Taman Nasional Teluk Cenderawasih, Papua Tengah, Indonesia, yang dijalankan oleh PT Pertamina International Shipping sejak 2021. Menggunakan data dari 32 informan pemangku kepentingan pada tujuh kelompok (2023–2025), studi ini memetakan empat belas outcome material yang mencakup pemantauan ekologis, pengelolaan sampah plastik, keselamatan menyelam komunitas, infrastruktur rantai dingin, dan edukasi konservasi. Total investasi program sebesar IDR 1.079.735.000 (Input), menghasilkan nilai kini outcome bersih sebesar IDR 2.429.384.408 dan rasio SROI 2,25:1. Berbeda dengan kerangka valuasi berbasis wisata, 73% nilai sosial total berasal dari jalur non-wisata, didominasi oleh nilai kelembagaan data pemantauan ilmiah (59,1%) dan pencegahan risiko paparan plastik. Delapan skenario analisis sensitivitas, termasuk penurunan 50% kunjungan wisatawan hiu paus, mengonfirmasi bahwa rasio tetap di atas titik impas (SROI minimum = 1,62), menunjukkan ketahanan struktural terhadap gangguan wisata. Temuan ini mendukung pembingkaian ulang konservasi laut berbasis komunitas sebagai investasi sosial strategis, bukan filantropi yang bergantung pada wisata, dengan implikasi bagi pembiayaan konservasi, manajemen risiko ESG korporat, dan strategi pendanaan SDG 14 di negara-negara Global South.